2017
DOI: 10.25165/j.ijabe.20171004.3219
|View full text |Cite
|
Sign up to set email alerts
|

Performances evaluation of four typical unmanned aerial vehicles used for pesticide application in China

Abstract: In recent years, unmanned aerial vehicles (UAVs) for plant protection have achieved rapid development in China. In order to test and evaluate the performances of pesticides application and development status of UAVs in China, four typical UAV models were selected to test the spraying coverage, penetrability, droplets density and the work efficiency. The results showed that the deposition and spraying liquid coverage were inconsistent both in lateral and longitudinal direction. Under the condition of the simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 7 publications
3
30
0
2
Order By: Relevance
“…Shilin et al . showed that UAV spray can improve the droplet distribution, coverage ratio and penetrability of pesticides . A similar phenomenon was also observed in this study, whereby the UAV and mister sprayer resulted in more depositions and better penetrability and uniformity compared to the two traditional spraying methods.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Shilin et al . showed that UAV spray can improve the droplet distribution, coverage ratio and penetrability of pesticides . A similar phenomenon was also observed in this study, whereby the UAV and mister sprayer resulted in more depositions and better penetrability and uniformity compared to the two traditional spraying methods.…”
Section: Resultssupporting
confidence: 87%
“…Li et al . showed that high‐volume conventional sprayers with coarse nozzles and low spray quality cause ineffective pesticide application, excessive pesticide residues and a high risk of operator exposure, while use of a UAV was found to increase application precision efficiency . Wang et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations